Study on Pathway of Benzo(a)pyrene Generation by Quantum Chemistry Calculations - Chen1, Yi-Lei; Wang2, Chuan-Ming (Asian Journal of Chemistry, 2014)
Density functional theory and Hatree-Fock method were employed to study the generation pathway of benzo(a)pyrene as a greatly carcinogenic substance at B3LYP and HF levels, respectively. By using 6-31G group to calculate the reaction pathways of acetylene polymerization and butenyne polymerization, we identified the transition state, intermediates and reaction energy barrier. We also calculated the energy barrier of styrene becoming butyl benzene via chain extension as well as the energy variation in the reaction of butyl benzene with tetrahydro-naphthalene to finally form benzo(a)pyrene. We concluded from our calculations that the aforesaid generation pathway of benzo(a)pyrene is theoretically possible and available.